Development and evaluation of a stepwise clinical competency development program for new nurses: A single-group repeated-measures quasi-experimental study - Shinhye Ahn; Hye Won Jeong (PLoS ONE, 2026)
Background New nurses often encounter adaptation challenges in hospital settings owing to gaps in clinical knowledge and skills, leading to high turnover rates and patient safety concerns. Although various orientation and preceptorship programs exist, they remain inconsistent and rarely evaluated longitudinally. Effective training is essential to support clinical adaptation. This study aimed to develop a structured, stepwise clinical competency development program (SCCDP) for new nurses and evaluate its effectiveness. Methods This study employed a single-group repeated-measures quasi-experimental design. From September 2023 to July 2024, 49 new nurses from C University Hospital in South Korea participated in the SCCDP, which consisted of lectures, practice, and simulation validated by experts. The outcomes measured included basic and advanced clinical knowledge, clinical performance ability, and self-efficacy at four intervals: pre-intervention, immediately post-intervention, and at three and six months post intervention. Data were analyzed using repeated-measures and Friedman’s ANOVA, and effect sizes were calculated. Results The SCCDP significantly improved new nurses’ basic clinical knowledge immediately post-intervention and three and six months post-completion (F = 40.01, p < .001), with the largest effect size observed in medical device operation (ES = 1.56–1.65). Advanced clinical knowledge also demonstrated significant enhancement across all time points (F = 26.06, p < .001), with the greatest increase occurring immediately after the SCCDP (ES = 1.84), particularly in emergency nursing (ES = 1.22). Clinical performance ability showed notable gains at three and six months post-program (χ² = 55.92, p < .001), with the most substantial improvement in interpersonal and communication skills (ES = 2.05–2.09). However, self-efficacy did not change significantly over time (F = 2.80, p = .066). Conclusions The SCCDP enhanced new nurses’ knowledge and clinical performance and demonstrated sustained effects over time. These findings support the implementation of structured, competency-based education to facilitate new nurses’ adaptation and retention in clinical practice.